Steel chair to the head the pleasure and pain of professional wrestling - Sammond, Nicholas 1960- (Duke University Press, 2005)
Introduction: a brief and unnecessary defense of professional wrestling / Nicholas Sammond -- The world of wrestling / Roland Barthes -- "Never trust a snake": WWF wrestling as masculine melodrama / Henry Jenkins III -- "Real wrestling"/"real" life / Sharon Mazer -- The hour of the mask as protagonist: El Santo versus the skeptics on the subject of myth / Carlos Monsiváis -- The mask of the Luchador: wrestling, politics, and identity in Mexico / Heather Levi -- Squaring the family circle: WWF smackdown assaults the social body / Nicholas Sammond -- "Ladies love wrestling too": female wrestling fans online / Catherine Salmon and Susan Clerc -- The "logic" of professional wrestling / Laurence De Garis -- Is raw war?: professional wrestling as popular s/m narrative -- Lucia Rahilly -- Not quite heroes: race, masculinity, and Latino professional wrestlers / Phillip Serrato -- Trading in masculinity: muscles, money, and market discourse in the WWF / Douglas Battema and Philip Sewell -- Afterword, part I: wrestling with theory, grappling with politics / Henry Jenkins III -- Afterword, Part II: growing up and growing more risqué / Henry Jenkins IV.